PERANCANGAN SISTEM PEMESANAN KATERING BERBASIS WEB PADA KATERING "MAKIJUL KATERING" - Syarifzul Hidayat (2023)
A web-based catering ordering system is a solution that is increasingly in demand in the catering industry to increase efficiency and convenience in the ordering process. The purpose of this final project is to design and develop an efficient and user-friendly web-based catering ordering system. In designing this system, an analysis of the needs of users and catering business owners was carried out, as well as research on the latest technologies and methods in web development. This system is designed to make it easier for customers to place catering orders through a web platform with an intuitive and responsive user interface. This catering ordering system includes important features, such as selecting menus, determining order quantities, selecting delivery dates and times, as well as integration with secure online payment methods. In addition, this system also provides efficient menu and stock management, order management, and report generation which helps business owners to better manage their business operations. It is hoped that with the implementation of this web-based catering ordering system, customers can easily place catering orders according to their needs, while catering business owners can improve operational efficiency, expand customer reach, and increase customer satisfaction. Periodic system testing and maintenance is also required to ensure optimal performance and system reliability.